Penguatan Pengembangan Upland Manggis sebagai Dukungan untuk Meningkatkan Produksi Manggis dan Pertumbuhan Ekonomi Wilayah - Sariyoga, Setiawan; Aliudin, Aliudin; Andi , Andi (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
Mangosteen is a prospective commodity to be developed in Lebak Regency. Socially and economically, mangosteen has been proven to be able to contribute to family welfare in Lebak Regency. This study aims to examine efforts to strengthen mangosteen commodities from production aspects from the legal, sociological, and burden aspects on the regional economy. The method used in this study is descriptive analysis. Data analysis techniques with Purposive sampling. Samples were selected based on the relevance and role of the population in completing the research theme. The number of selected samples was 9 samples. The results of the study show that from the legal, social and burden aspects on regional finances, mangosteen commodities can be developed in Lebak Regency. Mangosteen commodities have high importance and suitability for the economic growth of Lebak Regency. Important aspects to improve the performance of mangosteen commodities require support, namely regional regulations, ease of farmers to access agricultural credit, technical assistance, local financial institutions, marketing institutions, and supply chain development.